Are California Elementary School Test Scores More Strongly Associated With Urban Trees Than Poverty? - Tallis, Heather; Bratman, Gregory N.; Samhouri, Jameal F.; Fargione, Joseph (Frontiers in Psychology, 2018)
Greenspace around school grounds has been associated with benefits to students' cognitive function, providing an important ecosystem service. Questions remain regarding the size of this benefit relative to other factors, and which features of greenspace are responsible for these effects. We conducted a large-scale correlative study subsampling elementary schools (n = 495) in ecologically, socially and economically diverse California. After controlling for common educational determinants (e.g. socio-economic status, race/ethnicity, student teacher ratio, gender ratio) we found a significant, positive association between test scores and tree and shrub cover within 750m and 1000m of urban schools. Tree and shrub cover was not associated with test scores in rural schools or five buffers closer to urban schools (10m, 50m, 100m, 300m, 500m). Two other greenspace variables (NDVI and agricultural area) were not associated with test performance at any of the analyzed buffer distances for rural or urban schools. Minority representation had the largest effect size on standardized test scores (8.1% difference in scores with 2SD difference in variable), followed by tree and shrub cover around urban schools, which had a large effect size (2.9% - 3.0% at 750m and 1000m) with variance from minority representation and socioeconomic status (effect size 2.4%) included. Within our urban sample, average tree-cover schools performed 4.2% (3.9% - 4.4% 95% CI) better in terms of standardized test scores than low tree-cover urban schools. Our findings support the conclusion that neighborhood-scale (750m-1000m) urban tree and shrub cover is associated with school performance, and indicate that this element of greenspace may be an important factor to consider when studying the cognitive impacts of the learning environment. These results support the design of experimental tests of tree planting interventions for educational benefits.